Beyond Alkaloids: Novel Bioactive Natural Products From Lobelia Species - Zheng, Qinfang; Wang, Ye; Zhang, Shuihan (Frontiers in Pharmacology, 2021)
In this work, we reviewed the progress in the phytochemical and biological investigations of bioactive components derived from medicinally valuable Lobelia species. In the last 60 years, Lobelia has garnered significant attention from the phytochemist from around the world, majorly due to the discovery of bioactive piperidine alkaloids (e.g., lobinaline and lobeline) in the early 1950s. Later, lobeline underwent clinical trials for several indications including the treatment of attention deficit hyperactivity disorder and a multicenter phase three trial for smoking cessation. Subsequently, several other alkaloids derived from different species of Lobelia were also investigated for their pharmacological characteristics. However, in the last few years, the research focus has started shifting to the characterization of the other novel chemical classes. The major shift has been noticed due to the structurally similar alkaloid components, which essentially share similar pharmacological, physicochemical, and toxicological profiles. In this review, we present an up-to-date overview of their progress with special attention to understanding the molecular mechanisms of the novel bioactive components.